ANALYSIS OF FACTORS INFLUENCING THE RATIO OF HOUSING NON-PERFORMING LOAN FOR THE 2015-2024 PERIOD - zahra, talitha alea; Megapaksi, Girindra (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the internal and external factors influencing the non-performing financing (NPF) ratio of home ownership financing in Islamic commercial banks in Indonesia during the period 2015–2024. Internal factors analyzed include the BOPO ratio, and Capital Adequacy Ratio (CAR), while external factors consist of exchange rate, and money supply. The study employs secondary data and the Error Correction Model (ECM) method to examine both short-term and long-term effects of these variables on NPF. The results indicate that both internal and external factors simultaneously have a significant impact on the NPF of home ownership financing. These findings provide important implications for risk management in Islamic banks to maintain financing quality and support the stability of the Islamic banking sector in Indonesia .